Graphitic carbon-wrapped NiO embedded three dimensional nitrogen doped aligned carbon nanotube arrays with long cycle life for lithium ion batteries. Issue 50 (9th August 2018) - Deng, Weina; Chen, Xiaohua; Hu, Aiping; Zhang, Shiying
Abstract : NACNTs@NiO@graphitic carbon composites were synthesized with the help of nebulizing. The outstanding performances are attributed to the original structure of NACNTs@NiO@graphitic carbon. Abstract : In this work, a three-dimensional nitrogen doped aligned carbon nanotube array (NACNTs)@NiO@graphitic carbon composite was fabricated by an effective strategy involving nebulized ethanol assisted infiltration, In this structure, the NiO nanoparticles were wrapped by graphitic carbon layers and NiO@graphitic carbon core–shell nanoparticles adhered strictly to the surface of NACNTs to form a highly ordered 3D structure. When this composite was used as an anode for lithium ion batteries, the well-ordered pore of its NACNTs can facilitate the electrolyte to penetrate and improve electronic conductivity. At the same time, the graphitic layers can promote the stability of a solid electrolyte interface film. Therefore, the NACNTs@NiO@graphitic carbon composite containing 68.1 wt% NiO delivers excellent capacity retention of 91.6% after 200 cycles at 0.2C.